Additions of the flowering plants in the herbarium of Department of Plant Resources, Nepal (KATH), collected through Darwin Initiative Project (U.K.) in 2004 and 2005 - Rajbhandari, Keshab R.; Manandhar, Vaidya K.; Dahal, Sajan; Uprety, Rajesh K.; Pandey, Nirmala (Journal of Plant Resources, 2008)
As a part of the training programme of the Darwin Initiative Project (U.K.) on ‘Building capacity for plant biodiversity, inventory and conservation in Nepal', two botanical expeditions were conducted in Sagarmatha National Park, Solukhumbu District, East Nepal in 2004 and 2005 and one in Chitwan and adjoining areas, Central Nepal in 2004. In total about 1800 plant species were collected during these three expeditions. Among these, 158 species are new additions to the Herbarium of Department of Plant Resources (KATH). Keywords: plants; Nepal; UK. Bulletin of the Department of Plant Resources Vol 30, 2008 pp 22-46